Material Worlds: Genealogies of Race and Nature (Tufts Archival Research Center, 2018)
"Material Worlds: Genealogies of Race and Nature" by Mel Y. Chen, Associate Professor of Gender and Women's Studies at the University of California, Berkeley; Jake Kosek, Associate Professor of Geography at the University of California, Berkeley; and Alexander Blanchette, Assistant Professor of Anthropology, Tufts University.